2016
DOI: 10.1002/pbc.26104
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell histiocytosis is a neoplasm and consequently its recurrence is a relapse: In memory of Bob Arceci

Abstract: Langerhans cell histiocytosis (LCH) remains a poorly understood disorder with heterogeneous clinical presentations characterized by focal or disseminated lesions that contain excessive (where MEK and ERK are mitogen-activated protein kinase and extracellular signal-regulated kinase, respectively) pathway in nearly 100% of patients with LCH. Herein, we review the evidence that recurrent genetic abnormalities characterized by activating oncogenic mutations should satisfy prerequisites for LCH to be called a neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 97 publications
(213 reference statements)
0
27
0
Order By: Relevance
“…To the Editor: Egeler et al (PBC, June 2016) "reviewed the evidence that recurrent genetic abnormalities characterized by activated oncogenic mutations should satisfy prerequisites for Langerhans cell histiocytosis (LCH) to be called a neoplasm". 1 LCH patients with a worse prognosis are those who at diagnosis present with hematologic or hepatic involvement, frequently with high requirements of albumin and blood cells. Nevertheless, in those patients, no significant number of mitosis in the biopsies or clear cellular abnormalities was found that would be consistent with neoplasia.…”
Section: Is Langerhans Cell Histiocytosis a Neoplasia?mentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor: Egeler et al (PBC, June 2016) "reviewed the evidence that recurrent genetic abnormalities characterized by activated oncogenic mutations should satisfy prerequisites for Langerhans cell histiocytosis (LCH) to be called a neoplasm". 1 LCH patients with a worse prognosis are those who at diagnosis present with hematologic or hepatic involvement, frequently with high requirements of albumin and blood cells. Nevertheless, in those patients, no significant number of mitosis in the biopsies or clear cellular abnormalities was found that would be consistent with neoplasia.…”
Section: Is Langerhans Cell Histiocytosis a Neoplasia?mentioning
confidence: 99%
“…To the Editor: Egeler et al. (PBC, June 2016) “reviewed the evidence that recurrent genetic abnormalities characterized by activated oncogenic mutations should satisfy prerequisites for Langerhans cell histiocytosis (LCH) to be called a neoplasm” . If the definition of neoplasia is only related to the presence of somatic mutations, the previous definition is far from being controversial.…”
mentioning
confidence: 99%
“…Skin LCH frequently presents as refractory eczematous rash, whereas bone LCH usually causes osteolytic bone lesions with associated soft‐tissue masses . Genomic analysis has recently redefined our view of histiocytoses and LCH is now commonly defined as a clonal neoplasm driven by constitutive activation of MAPK signaling . In 50–60% of cases, the MAPK activation is driven by the BRAF V600E mutation …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proposed that LCH is a neoplasm. This is supported by the demonstration of clonality of LCH cells, driver somatic mutations in BRAF in up to 55% of patients with LCH, and activation of the RAS‐RAF‐MEK‐ERK pathway in nearly 100% of patients with LCH …”
Section: Introductionmentioning
confidence: 82%